In dialogue with artist Laura Anderson Barbata – Interview (Palíndromo, 2024)
This interview aims to reflect on the creative process of artist Laura Anderson Barbata, born in Mexico City/Mexico and who currently lives and works between New York/USA and Mexico City. Transdisciplinary artist, author of several books, works in different artistic languages, and has held exhibitions in countries such as Mexico, the United States and Brazil. The dialogue proposed in this interview with Laura Anderson Barbata, addresses border transits and displacements, the sense of belonging, the relationships between the global and the local, intone her artistic creations that combine different narratives and protagonisms. Hoping to contribute to the dissemination of his work, we embarked on this dialogue, in a conversation about his trajectory, experiences and artistic practices as possibilities for new ties between artists, knowledge and languages
Keywords: Laura Anderson Barbata; contemporary art; artistic creation; displacements